Characteristics of Disease Profile of Hospitalized adult patients Referred to the Cardiology Department in a Tertiary Care Orthopedics Hospital - Siddiqui, Md Ali Ehsan; Islam, Dewan Mohammad Karimul; Huda, S M Nazmul; Ullah, A Z M Ahsan (Bangladesh Journal of Medicine, 2024)
Objectives: For patients admitted to a tertiary care orthopedic hospital, cardiac consultation is a common practice and almost essential in every country. This is because of the increased morbidity and mortality of cardiac cases, especially during the perioperative period. The study was conducted to understand and evaluate the common causes of referral and to discover the disease profile pattern of referred cases to the cardiology department in this hospital.Methods: This prospective observational study was carried out in the cardiology department, NITOR hospital, (National Institute of Traumatology and Orthopedics Rehabilitation) in Sher-E-Bangla Nagar, Dhaka, from July 2022 to December 2022. After data collection, data analysis was done using the SPSS-22 version, and findings were expressed in frequency and percentage. Results: This study revealed that the majority of referred cases were routine and non-cardiac (75%), with normal LV function on echo.Non cardiac cases were referred for the fitness of general anesthesia. Among cardiac cases, hypertension (9%) got the highest referral; followed by OMI (4%), ICM (2.4%), congenital heart disease (2.2%), ventricular heart disease (2.4%), arrhythmia (1.8%), ACS (2.4%), pulmonary embolism (0.3%), and others (0.4%).Conclusion:Cardiac problems, morbidity, and mortality are increasing day by day. So every different tertiary care hospital should have an enriched cardiology department with an efficient team and proper instrumental support. Bangladesh J Medicine 2024; 35: 93-95